Protective Effect of Klotho against Ischemic Brain Injury Is Associated with Inhibition of RIG-I/NF-κB Signaling - Zhou, Hong-Jing; Li, Hui; Shi, Meng-Qi; Mao, Xiao-Na; Liu, Dong-Ling; Chang, Yi-Ran; Gan, Yu-Miao; Kuang, Xi; Du, Jun-Rong (Frontiers in Pharmacology, 2018)
Aging is the greatest independent risk factor for the occurrence of stroke and poor outcomes, at least partially through progressive increases in oxidative stress and inflammation with advanced age. Klotho is an antiaging gene, the expression of which declines with age. Klotho may protect against neuronal oxidative damage that is induced by glutamate. The present study investigated the effects of klotho overexpression and knockdown by an intracerebroventricular injection of a lentiviral vector that encoded murine klotho (LV-KL) or rat klotho short-hairpin RNA (LV-KL shRNA) on cerebral ischemia injury and the underlying anti-neuroinflammatory mechanism. The overexpression of klotho induced by LV-KL significantly improved neurobehavioral deficits and increased the number of live neurons in the hippocampal CA1 and caudate putamen subregions 72 h after cerebral hypoperfusion that was induced by transient bilateral common carotid artery occlusion (2VO) in mice. The overexpression of klotho significantly decreased the immunoreactivity of glial fibrillary acidic protein and ionized calcium binding adaptor molecule-1, the expression of retinoic-acid-inducible gene-I, the nuclear translocation of nuclear factor-B, and the production of proinflammatory cytokines (tumor necrosis factor  and interleukin-6) in 2VO mice. The knockdown of klotho mediated by LV-KL shRNA in the brain exacerbated neurological dysfunction and cerebral infarct after 22 h of reperfusion following 2 h middle cerebral artery occlusion in rats. These findings suggest that klotho itself or enhancers of klotho may compensate for its aging-related decline, thus providing a promising therapeutic approach for acute ischemic stroke during advanced age.